2019
DOI: 10.1186/s12885-019-6278-9
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-resistant triple-negative breast cancer subtypes: multiple mechanisms of resistance

Abstract: BackgroundUnderstanding mechanisms underlying specific chemotherapeutic responses in subtypes of cancer may improve identification of treatment strategies most likely to benefit particular patients. For example, triple-negative breast cancer (TNBC) patients have variable response to the chemotherapeutic agent cisplatin. Understanding the basis of treatment response in cancer subtypes will lead to more informed decisions about selection of treatment strategies.MethodsIn this study we used an integrative functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 74 publications
4
73
0
Order By: Relevance
“…Interestingly, mCAFs are highly associated with a stroma-derived invasion signature predictive of responsiveness to neoadjuvant chemotherapy in breast cancer [18]. Numerous clinical trials are currently revaluating cisplatin as chemotherapeutic option to treat TNBC, especially those harbouring a BRCA mutation [24,33]. As expected, our data show that lower BRCA1 expression is found in cisplatin responder patients, compared to non-responders.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, mCAFs are highly associated with a stroma-derived invasion signature predictive of responsiveness to neoadjuvant chemotherapy in breast cancer [18]. Numerous clinical trials are currently revaluating cisplatin as chemotherapeutic option to treat TNBC, especially those harbouring a BRCA mutation [24,33]. As expected, our data show that lower BRCA1 expression is found in cisplatin responder patients, compared to non-responders.…”
Section: Discussionsupporting
confidence: 79%
“…The cytotoxicity of complexes 1a and 2a towards TNBC's is quite promising as these cell lines are typically cisplatin resistant. 75,76 Drug resistance is an ever-increasing problem in medicine so developing therapeutics for refractory tumours is of great importance. 77 To test the selectivity of compounds 1a and 2a for cancer cells over normal cells, we evaluated these complexes in the normal retinal epithelial cells using the MTT assay.…”
Section: Anticancer Activity In Vitromentioning
confidence: 99%
“…Cisplatin is a platinum-based chemotherapy that demonstrated efficacy as a first-line chemotherapy in TNBC patients ( 117 ). However, multiple mechanisms of cisplatin-resistance have been identified in TNBC cells ( 118 ). Despite the potential deleterious effects of oleic acid on TNBC cells, one study demonstrated a potential synergistic relationship between oleate and Cisplatin on inducing apoptosis in MDA-MB-231 cells ( 68 ).…”
Section: Olive Oil and Tnbc: Reviewmentioning
confidence: 99%